Investigation of the origin and spread of a mammalian transposable element based on current sequence diversity - Hellen, Elizabeth H.B.; Brookfield, John F.Y. (Springer, 2011)
Almost half the human genome consists of mobile DNA elements, and their analysis is a vital part of understanding the human genome as a whole. Many of these elements are ancient and have persisted in the genome for tens or hundreds of millions of years, providing a window into the evolution of modern mammals. The Golem family have been used as model transposons to highlight computational analyses which can be used to investigate these elements, particularly the use of molecular dating with large transposon families. Whole-genome searches found Golem sequences in 20 mammalian species. Golem A and B subsequences were only found in primates and squirrel. Interestingly, the full-length Golem, found as a few copies in many mammalian genomes, was found abundantly in horse. A phylogenetic profile suggested that Golem originated after the eutherian–metatherian divergence and that the A and B subfamilies originated at a much later date. Molecular dating based on sequence diversity suggests an early age, of 175 Mya, for the origin of the family and that the A and B lineages originated much earlier than expected from their current taxonomic distribution and have subsequently been lost in some lineages. Using publically available data, it is possible to investigate the evolutionary history of transposon families. Determining in which organisms a transposon can be found is often used to date the origin and expansion of the families. However, in this analysis, molecular dating, commonly used for determining the age of gene sequences, has been used, reducing the likelihood of errors from deleted lineages.